Multifunctional properties of bio-poly(butylene succinate) reinforced with multiwalled carbon nanotubes - Krasinskyi, Volodymyr; Bajer, Krzysztof; Dulebova, Ludmila; Polychronopoulos, Nickolas; Krasinska, Oksana; Kaczor, Daniel (Beilstein Journal of Nanotechnology, 2025)
Recent advances in nanocomposite technology, particularly the incorporation of carbon nanotubes, have shown promise in enhancing the properties of biodegradable polymers. This study investigated the effect of a 0.5 wt % addition of multiwalled carbon nanotubes (MWCNTs) on the properties of bio-poly(butylene succinate) (BioPBS) using a masterbatch-based melt compounding method. The incorporation of MWCNTs enhanced the mechanical strength and stiffness, improved the tribological properties by reducing friction, and increased the crystallization temperature. However, it also resulted in a decrease in elasticity. Morphological analysis confirmed the uniform dispersion of the nanotubes. These findings underscore the potential of MWCNTs to tailor the properties of BioPBS for specific applications, such as in the packaging, automotive, and biomedical industries, where both biodegradability and enhanced material performance are desirable.
Keywords: melt compounding; multiwalled carbon nanotubes; poly(butylene succinate); structure; tribological properties